Evaluating information technology investments - a survey of Kenyan Commercial Banks - (:unkn) unknown (My University, 2015)
This study attempts to provide empirical evidence on the current state of practice in Kenyan banking institutions in evaluating IT investments ex ante. Results of the survey show that the most popular investment appraisal techniques used in such evaluation in Kenyan banks are cost-benefit analysis, technical arguments, risk analysis, competition, payback period and return on investment, while the least popular are the Internal Rate of Return, computer-based techniques and Net Present Value. The fundamental conclusion of this research is that in the banking industry, the level of usage of sophisticated techniques that integrate financial and strategic analysis to appraise IT investment is low compared to the usage of “traditional” appraisal techniques that focus on the financial return of an investment. Results of this study will help to establish banking industry-wide benchmarks and best practices in
Proceedings of the 10th Annual Conference ©2009 IAABD
This study attempts to provide empirical evidence on the current state of practice in Kenyan banking institutions in evaluating IT investments ex ante. Results of the survey show that the most popular investment appraisal techniques used in such evaluation in Kenyan banks are cost-benefit analysis, technical arguments, risk analysis, competition, payback period and return on investment, while the least popular are the Internal Rate of Return, computer-based techniques and Net Present Value. The fundamental conclusion of this research is that in the banking industry, the level of usage of sophisticated techniques that integrate financial and strategic analysis to appraise IT investment is low compared to the usage of “traditional” appraisal techniques that focus on the financial return of an investment. Results of this study will help to establish banking industry-wide benchmarks and best practices in